Variation in piRNA and Transposable Element Content in Strains of Drosophila melanogaster. - Song, J.; Liu, J.; Schnakenberg, S.L.; Ha, H.; Xing, J.; Chen, K.C. (Genome biology and evolution, 2014)
Transposable elements (TEs) are one of the most important features of genome architecture, so their evolution and relationship with host defense mechanisms have been topics of intense study, especially in model systems such as Drosophila melanogaster. Recently, a novel small RNA-based defense mechanism in animals called the Piwi-interacting RNA (piRNA) pathway was discovered to form an adaptive defense mechanism against TEs. To investigate the relationship between piRNA and TE content between strains of a species, we sequenced piRNAs from 16 inbred lines of D. melanogaster from the Drosophila Genetic Reference Panel. Instead of a global correlation of piRNA expression and TE content, we found evidence for a host response through de novo piRNA production from novel TE insertions. Although approximately 20% of novel TE insertions induced de novo piRNA production, the abundance of de novo piRNAs was low and did not markedly affect the global pool of ovarian piRNAs. Our results provide new insights into the evolution of TEs and the piRNA system in an important model organism.